Implementasi Program Suroboyo Bus Dalam Mengurangi Kemacetan Di Kota Surabaya - Viona Erlanda; Radjikan Radjikan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Large cities in Indonesia are not exempt from severe traffic congestion problems. This occurs because people feel more comfortable and dependent on using private motorcycles and cars. Public transportation in Indonesia aims to help reduce congestion, decrease pollution, and save on expenses. This type of research uses the literature study method and employs a qualitative approach because the data generated are in the form of words or descriptions. In the data collection process, researchers combine information that aligns with the topic or issue being studied, which is obtained from research reports, books, and journals. According to the theory of Donald van Metter and Carl van Horn, with six variables consisting of policy size and objectives, resources, characteristics of implementing agents, disposition of implementers, organizational communication and activities, as well as economic, social, and political environment, it can be concluded that the existence of the Suroboyo Bus as one strategy to tackle congestion in Surabaya has not yet been effective. However, there has been an increase in the number of passengers each year. It is hoped that more people will use public transportation to solve congestion issues, and that the government will further innovate the Suroboyo Bus so that people will have more interest in using this public transportation.